Perjuangan Hidup Tokoh Utama Novel 23 Episentrum Karya Adenita dan Relevansinya terhadap Materi Ajar Sastra di SMA Tinjauan Sosiologi Sastra - Widya Prameswari Pertiwi; Imam Muhtarom; Dewi Herlina Sugiarti (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this research was to describe the social context based on the influence on the life struggle of the main character of the novel 23 Episentrum by Adenita. In addition to describing the social context, this study also explores the elements of story building. This research is a type of qualitative research, so the method used is descriptive analysis, namely presenting data by relying on interpretations to become a description. The object of this research is the intrinsic element and social context. The data source of this research is the novel 23 Episentrum by Adenita. The data collection techniques of this research are reading, note-taking, and documentation techniques. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The results obtained from the research show that (1) the analysis of the main character's life struggle includes the struggle to survive, always be grateful, realize dreams, pay off debts, run jobs, get happiness, and to continue a good. (2) analysis of the social context that affects the main character includes the influence of the family environment, friendships, and work. The results of this study are relevant to literature teaching materials in high school.